Burnout Profile of Indonesian Students: A Study of Measurement Tool Development and Latent Profile Analysis - Afifah, Sabrina Puti; Lenggogeni, Puti; Mubarrak, Kemas Rahmat; Halim, Angeline Freshbi Chesa; Zhafirah, Salwa (Gadjah Mada Journal of Psychology (GamaJoP), 2026)
Academic burnout among university students is a critical issue because it significantly impacts both psychological well-being and academic performance. This study aims to develop a culturally relevant academic burnout scale tailored to the higher education context in Indonesia and to identify latent student profiles based on their burnout experiences. A total of 222 active students from various universities in Indonesia participated in this study. Construct validity of the scale was tested using confirmatory factor analysis (CFA), while profile analysis was conducted through latent profile analysis (LPA). The results indicated that the academic burnout scale comprises three main dimensions (exhaustion, cynicism, and inefficacy), with a total of 12 items, and meets the goodness-of-fit criteria with RMSEA < 0.08, CFI & TLI > 0.90, and SRMR < 0.08. The measurement results also demonstrated good reliability, as indicated by McDonald’s Omega (ω = 0.853). The profile analysis identified two latent student classes: the high-burnout group and the low-burnout group. These findings highlight the importance of employing contextually appropriate measurement tools and person-centered approaches in understanding the dynamics of academic burnout among Indonesian university students.